Privileged to Kill: Bill Gastner #5 - Havill, Steven (New York : St. Martin's press, 1997)
A drifter Gasnter helps becomes the prime suspect when a child's body is found.
"A Thomas Dunne book."
New Book Winter 2024.
Keywords: Gastner, Bill (Fictitious character) -- Fiction; Posadas County (N.M. : Imaginary place) -- Fiction; Sheriffs -- Fiction -- New Mexico; Children -- Crimes against -- Fiction; Homeless persons -- Fiction; New Mexico -- Fiction; Mystery fiction